THE IDENTIFICATION OF MICRO FACTORS ON VALUE OF MANUFACTURING COMPANY - Permata, Irma Sari (Journal of Research in Business, Economics, and Education, 2019)
The purpose of the company's microanalysis is to know the internal condition of the company as a whole so that it can assess the development of the good condition of a bad company. The things analyzed in microanalysis include several micro factors, such as firm size, profitability level, liquidity, capital structure, efficiency and effectiveness of management performance and so on. These conditions can be seen in the company's financial data and financial data of the company is reflected in the financial statements. The results of this study prove that Liquidity (X1), Solvency (X2), Profitability (X3), Dividend (X4) and Size Company (X5) variables partially or simultaneously have a significant effect on the dependent variable of Company Value (Y).